PERIODICALS AS AN ELEMENT OF CIVIL SOCIETY IN ECONOMIC SPHERE OF THE NORTH CAUCASUS IN THE 60-70s OF THE 19th CENTURY (ON THE EXAMPLE OF «TERSKIE VEDOMOSTI») - S. A. AYLAROVA (Кавказология, 2019)
The article contains analysis of the material of economic character published in unofficial part of «Terskije vedomosti» in 60-70-s of the 19th century. Information potential of the official edition of Terski region; the importance of news paper material for investigation of join activity and unification of the efforts of the authorities and society towards modernization of the North-Caucasian region and formation of civil society are revealed. Regional peculiarities of economic modernization which found reflection in the newspaper material are defined. Information in the state of the main spheres of post-reform period regional economic (industry, agriculture, commerce, transport, finance) found reflection in several types of publications: articles, statistics, archive and reference material, notices, reports agroclimatic monitoring.  Abundance of material of economic-instructive character about the ways of improving of agricultural situation, popularization of new market forms of labour enables to speak about interested attitude of terskiy society to the problems of economic modernization and understanding of the ways of their solution. Post-reform changes made «Terskije vedomosti»  as a bearer of operative economic information a part of a new capitalist economic system. Subject and thematic analysis allows to overcome underestimation of the newspaper in the soviet period both as a historical source and as a factor of economic modernization in the region.